Feasibility analysis of hydrogen production potential from rooftop solar power plant for industrial zones in Vietnam. (November 2022) - Phap, Vu Minh; Sang, Le Quang; Ninh, Nguyen Quang; Binh, Doan Van; Hung, Bui Bao; Huyen, Cu Thi Thanh; Tung, Nguyen Thanh
Abstract: Currently, global energy transformation and the promotion of renewable energy use are being taken care of to minimize the harm to the environment. However, the disadvantage of renewable energy is the random change, which leads to the regulation of grid operations, which is very difficult when the capacity of renewable energy sources accounts for a large proportion. The hydrogen production technology from wind and solar energy sources is one of the possible methods to minimize adverse impacts on the utility grid and serve the load demand of industrial zones. In this study, the photovoltaic (PV) hydrogen production potential for industrial zones in Vietnam is analyzed. The Homer was used to simulate and calculate power output. The results showed that the Hai Duong province has the lowest solar radiation, so the solar power output is 3600389 kWh/year, and the amount of hydrogen generated is less so it mainly serves the hydrogen load while the fuel cell can only generate very low amounts of electricity of about 4150 kWh/year for direct current (DC) load. The hybrid power systems in the typical industrial plant in Quang Nam province, Binh Thuan province, Can Tho city can generate about 17386 kg/year to 17422 kg/year to supply the operation of fuel cells based on the value of solar radiation of each province. The better the area with solar potential, the lower the net present cost (NPC), cost of energy (COE), and operation cost, so the economical and technical efficiency of the PV–Fuel cell hybrid power system will increase. Highlights: Renewable power and hydrogen are a viable solution to serve the load demand in industrial parks and reduce environmental pollution. The area with the best solar energy potential such as Binh Thuan province has the lowest NPC, O&M costs, investment costs, and COE. Hai Duong province with the lowest solar energy potential has an insufficient amount of hydrogen for fuel cell operation. Use of solar power systems and fuel cells will help the industry plant to reduce greenhouse gas emissions.